Prevalence of Campylobacter spp. in Chicken from Retail Markets in Nakhon Pathom Province - Chalermkiat Saengthongpinit; Srisamai Viriyarampa; Thavajchai Sakpuaram (Agriculture and Natural Resources, 2005)
Campylobacter is a major food-borne pathogen, causing gastroenteritis characterized by watery and/or bloody diarrhea in humans. In general, poultry and poultry products are source of Campylobacter contamination. Information concerning prevalence of Campylobacter is useful for a strategic planning to reduce the contamination into the food chain. The aim of this study was to investigate the prevalence of chicken Campylobacter from retail markets in Nakhon Pathom province, Thailand. A total of 119 chicken samples, 71 chicken meat and 48 gizzards, were examined for the presence of Campylobacter spp. The result showed that 61.34% of the samples were contaminated with Campylobacter spp., of which 59.15% and 64.58% were found in chicken meat and gizzards, respectively. From the total of 73 positive samples, 94.52% were C. jejuni and 5.48% were C. coli. The result showed a high prevalence of Campylobacter spp. in chicken from the retail markets. Therefore, consumption and safe handling of raw chicken meat from retail market needed to be emphasized for control of this zoonotic enteric pathogen from poultry to human.